INFLUENCE OF COUNSELING WITH LEAFLETS BY PHARMACISTS ON THE LEVEL OF KNOWLEDGE, COMPLIANCE, AND BLOOD SUGAR LEVELS OF TYPE 2 DM PATIENTS IN KREMBUNG HEALTH CENTER IN SIDOARJO REGENCY - Dyah Ayu Febiyanti; Antonius Adji Prayitno; Yosi Irawati Wibowo (STIKES Rumah Sakit Anwar Medika, 2022)
Abstract Background: The high number of diabetes mellitus patients in Indonesia followed by low levels of knowledge and adherence to treatment causes the number of cases of complications due to high blood sugar levels, especially in Health Center increases. Method:This study uses pre-experimental research methods, with a one-group pretest-posttest research design before and after counseling with a leaflet media by pharmacists at Krembung Health Center of Sidoarjo Regency with a sample number of 34 subjects. The research instruments used sociodemographic questionnaires, Diabetes Knowledge Questionnaire (DKQ-24), and modified Morisky Medication Adherence Scale (MMAS) questionnaires. Results and analysis : Chi-square statistical test results at the level of knowledge and compliance, showed there was an influence on the increase in knowledge with a p-value of 0.001, and increased adherence to drugs with a p-value of 0.006, the results of T-test statistical tests also showed an influence on the decline in the value of FPG pre and post with a p-value of 0.002, and HbA1c pre and post values had a p-value of 0.001. Discussion: Patients experienced an increase in compliance after getting counseling with leaflets from 67.7% to73.5% which was statistically significant in addition to an increase in knowledge that caused patients to be more adherence to take drugs so that there was a significant decrease in the mean value of FPG pre 183.32 to FPG post 148.23 significantly and a significant decrease in the value of HbA1c from 8.45 to 7.03. Conclusion: Counseling education with leaflets by pharmacists is influential in increasing knowledge, adherence with drug use, and lowering blood sugar levels (FPG& HbA1c) of type 2 DM patients in Krembung Health Center of Sidoarjo Regency.